2018
DOI: 10.1103/physreva.97.063825
|View full text |Cite
|
Sign up to set email alerts
|

Wave scattering from two-dimensional self-affine Dirichlet and Neumann surfaces and its application to the retrieval of self-affine parameters

Abstract: Wave scattering from two-dimensional self-affine Dirichlet and Neumann surfaces is studied for the purpose of using the intensity scattered from them to obtain the Hurst exponent and topothesy that characterize the self-affine roughness. By the use of the Kirchhoff approximation a closed form mathematical expression for the angular dependence of the mean differential reflection coefficient is derived under the assumption that the surface is illuminated by a plane incident wave. It is shown that this quantity c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 94 publications
(172 reference statements)
0
9
0
Order By: Relevance
“…Figure 7 compares results for the glass scattering system for s-and p-polarization with a polar angle of incidence of θ 0 = 26°, when the reconstruction is performed on the basis of either the iterative or non-iterative reconstruction approaches, that is, on the basis of the expressions in Eqs. (15) or (16). From the results presented in this figure, several interesting observations should be made.…”
Section: B Computer Generated Scattering Datamentioning
confidence: 81%
See 3 more Smart Citations
“…Figure 7 compares results for the glass scattering system for s-and p-polarization with a polar angle of incidence of θ 0 = 26°, when the reconstruction is performed on the basis of either the iterative or non-iterative reconstruction approaches, that is, on the basis of the expressions in Eqs. (15) or (16). From the results presented in this figure, several interesting observations should be made.…”
Section: B Computer Generated Scattering Datamentioning
confidence: 81%
“…It should be remarked that for the input scattering data presented in Fig. 5, only marginal changes are found in the results of the reconstruction by basing it on the iterative approach (15), as compared to using the non-iterative approach (16) to produce the results presented in this figure. It should also be mentioned that for the numerous reconstruction tests that we have performed based on scattering data produced by computer simulations, we have found that the accuracy in the reconstruction of the correlation functions typically is the same, or better, than the accuracy in the reconstruction of the surface roughness.…”
Section: B Computer Generated Scattering Datamentioning
confidence: 91%
See 2 more Smart Citations
“…An interesting limit is obtained in the case of power-law correlations which can also be considered as a continuum of characteristic length scales. This case of long-ranged height correlations corresponds to selfaffine surfaces [39,[69][70][71]. Such surfaces have the particular property to remain statistically invariant by the family of anisotropic transformations: r → λr, z → λ H z where λ is a positive real scaling factor and H an exponent usually in the range [0, 1].…”
Section: Auto-correlation Functionmentioning
confidence: 99%